Κοινά βιώματα και εμπειρίες Ελλήνων και Σέρβων στη δημοτική ποίηση: Το παράδειγμα των δημοτικών τραγουδιών «Του νεκρού αδελφού» και «Ηκόρη και τ’ αδέλφια της» (Браћа и Сестра) - Ιωάννης Κιορίδης; Χρήστος Χαρακόπουλος; Τασούλα Τσιλιμένη; JASNA STOJANOVIC (Προσεγγίσεις και εστιάσεις στον Νέο Ελληνισμό: κείμενα, εικόνες, αντικείμενα, ιστορίες, 2025)
The experiences of the Balkan peoples are common, as reflected in the folk songs of their countries. The purpose of this study is to present the common cultural elements and moral social codes of the Greeks and Serbs, as they were shaped in the historical context of the time and are evident in the folk songs "The dead brother" and "The daughter and her brothers" (Браћа и Сестра/lat. Braća i Sestra). In more detail, this comparative study presents similarities in the lives of Greeks and Serbs, in terms of the institution of the family, family ties, the marriage custom, the social status of women, the common experience of being abroad, but also other issues, such as belief in the change of fortune, belief in the power of the oath, and the treatment of death. Finally, a brief reference is made to the common theme of the above songs with similar folk songs from other Balkan countries, which demonstrates the common beliefs and perceptions of the people of the region.